Development of a ‘Fish Tail’ Rudder to Improve a Ship’s Maneuverability in Seaway - Aries Sulisetyono (Institut Teknologi Sepuluh Nopember, 2014)
The maneuverability of a ship at seaway is strongly influenced by a design of rudder. An innovative design of rudder based on a tail shape of fish was developed with the intent of improving an efficiency of ship maneuverability. Two designs of rudders were proposed i.e. the rudder of forked which is a rudder with an area reduction on the middle part, and the lanceolate shape or a rudder with additional area on the middle part. In evaluation of the rudder designs performance, the numerical approach of Computational Fluid Dynamic (CFD) was applied to determine a side force generated by rudder using the commercial software of FLUENT. Numerical simulations were performed on the rudder designed of rectangular, forked and lanceolate which had similar a surface area with the variations of rudder angle such as 100, 200 and 300 due to the uniform fluid flow at a constant speed. Further simulations was performed on the two forked rudder designed which takes into account the influence of propeller due to fluid flow on the rudder surface. It had shown the velocity of fluid flow behind the shaft of propeller very small in which the middle part of the rudder produced less lift force compare to the other part of rudder. Mathematical and numerical model of ship maneuvering were developed in order to evaluate the performance of a ship maneuvering in seaway based on the IMO standards on turning test. The simulation results had shown the rudder of forked produce the ship maneuvering performance that exceeds the performance of rectangular rudder as well as lanceolate rudder.